The effect of a standardised source of divided attention in airway management: A randomised, crossover, interventional manikin study - Prottengeier, Johannes; Petzoldt, Marlen; Jess, Nikola; Moritz, Andreas; Gall, Christine; Schmidt, Joachim; Breuer, Georg (European Journal of Anaesthesiology, 2016)
Dual-tasking, the need to divide attention between concurrent tasks, causes a severe increase in workload in emergency situations and yet there is no standardised training simulation scenario for this key difficulty.We introduced and validated a quantifiable source of divided attention and investigated its effects on performance and workload in airway management.A randomised, crossover, interventional simulation study.Center for Training and Simulation, Department of Anaesthesiology, Erlangen University Hospital, Germany.One hundred and fifty volunteer medical students, paramedics and anaesthesiologists of all levels of training.Participants secured the airway of a manikin using a supraglottic airway, conventional endotracheal intubation and video-assisted endotracheal intubation with and without the Paced Auditory Serial Addition Test (PASAT), which served as a quantifiable source of divided attention.Primary endpoint was the time for the completion of each airway task. Secondary endpoints were the number of procedural mistakes made and the perceived workload as measured by the National Aeronautics and Space Administration's task load index (NASA-TLX). This is a six-dimensional questionnaire, which assesses the perception of demands, performance and frustration with respect to a task on a scale of 0 to 100.All 150 participants completed the tests. Volunteers perceived our test to be challenging (99%) and the experience of stress and distraction true to an emergency situation (80%), but still fair (98%) and entertaining (95%). The negative effects of divided attention were reproducible in participants of all levels of expertise. Time consumption and perceived workload increased and almost half the participants make procedural mistakes under divided attention. The supraglottic airway technique was least affected by divided attention.The scenario was effective for simulation training involving divided attention in acute care medicine. The significant effects on performance and perceived workload demonstrate the validity of the model, which was also characterised by high acceptability, technical simplicity and a novel degree of standardisation.
EVALuna2:5546